Relationship Between Compliance With Health Protocols Against ANC Visits In Pregnant Women In The Pandemic Period Of Covid-19 - Yanti, Ariu Dewi; Marifah, Asirotul; Suryantini, Naning Puji (Kirana Publisher (KNPub), 2022)
Background: The Covid 19 pandemic situation has hurt many sectors, including in the health sector, especially in maternal and infant health services. On the other hand, during Antenatal Care, pregnant women are afraid to come to health facilities because they are so scared of contracting them not to have their pregnancy checked. It can endanger the pregnancy of the mother or the fetus during pregnancy because it cannot detect the dangerous signs of pregnancy early.Objectives: The study aims to analyze the relationship between the protocols for implementing health protocols on ANC visits to pregnant women during the Covid-19 pandemic in the PMB area of Mojokerto Regency in 2020.Research Methods: This research method is to use an analytical design using a cross-sectional approach. The sampling technique used accident sampling, a total of 60 pregnant women.Results: The results of the study using Chi-Square analysis showed that there was no relationship between educational variables and ANC visits (ρ-value = 0.087> 0.05); there was a relationship between work variables and ANC visits (ρ-value = 0.001 <0.05), and there was no relationship. The adherence variable applied the Health Protocol with ANC visits (ρ-value = 0.457> 0.05).Conclusion: This study concludes that there is no relationship between compliance with implementing the Health Protocol with ANC visits to pregnant women during the Covid 19 period.